Remodeling of Rectal Innervation After Pullthrough Surgery for Hirschsprung Disease: Relevance to Criteria for the Determination of Retained Transition Zone. (July 2019) - Kapur, Raj P; Arnold, Michael A; Conces, Miriam R; Ambartsumyan, Lusine; Avansino, Jeffrey; Levitt, Marc; Wood, Richard; Mast, Kelley J
Background: After pullthrough surgery for Hirschsprung disease (HSCR), Glut1-positive submucosal nerve hypertrophy is used to diagnose retained transition zone in the neorectum. We hypothesized that pelvic nerves, severed during pullthrough surgery, sprout into the neorectum to mimic transition zone. Methods: The density (nerves/100x field) and maximum diameter of Glut1-positive submucosal nerves were measured in biopsies and redo resections from 20 patients with post-pullthrough obstructive symptoms. Their original and/or redo resections excluded unequivocal features of transition zone (myenteric hypoganglionosis or partial circumferential aganglionosis) in 17. Postoperative values were compared with control data from 28 cadaveric and 6 surgical non-HSCR specimens, and 14 primary HSCR resections. When possible, nerves were tracked from attached native pelvic soft tissue or aganglionic rectal cuff into the pulled-through colon. Results: Glut1-positive submucosal nerves were not present in the 11 colons of non-HSCR infants less than 1 year of age, except sparsely in the rectum. In 17 older non-HSCR controls, occasional Glut1-positive nerves were observed in prerectal colon and were larger and more numerous in the rectum. In redo resections, Glut1-positive submucosal innervation in post-pullthrough specimens did not differ significantly from age-appropriate non-HSCR rectal controls and pelvic Glut1-positive nerves were never observed to penetrate the pulled-through colon. However, the density and caliber of Glut1-positive nerves in the neorectums were significantly greater than expected based on the prerectal location from which the pulled-through bowel originated. Conclusions: Submucosal innervation in post-pullthrough specimens does not support the hypothesis that native pelvic nerves innervate the neorectum, but suggests remodeling occurs to establish the age-appropriate density and caliber of rectal Glut1-positive innervation. The latter should not be interpreted as transition zone pullthrough in a rectal biopsy from a previously done pullthrough.